2007
DOI: 10.1111/j.1365-2672.2006.03039.x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid PCR procedure for the specific identification of Lactobacillus sanfranciscensis, based on the 16S-23S intergenic spacer regions

Abstract: Aims:  The organization of ribosomal RNA (rrn) operons in Lactobacillus sanfranciscensis was studied in order to establish an easy‐to‐perform method for identification of L. sanfranciscensis strains, based on the length and sequence polymorphism of the 16S‐23S rDNA intergenic spacer region (ISR). Methods and Results:  PCR amplification of the 16S‐23S rDNA ISRs of L. sanfranciscensis gave three products distinguishing this micro‐organism from the remaining Lactobacillus species. Sequence analysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 59 publications
2
28
0
2
Order By: Relevance
“…Bacterial DNA was extracted using an Archive Pure DNA Purification System (5 PRIME) according to the manufacturer's instructions. A preliminary identification was performed through the recognition of the electrophoretic profile generated from the amplification of internal ribosomal spacers according to Valcheva et al (2007). Furthermore, all the strains were subjected to the sequencing of a portion of the 16S rRNA-coding gene in order to confirm that they belonged to the species.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial DNA was extracted using an Archive Pure DNA Purification System (5 PRIME) according to the manufacturer's instructions. A preliminary identification was performed through the recognition of the electrophoretic profile generated from the amplification of internal ribosomal spacers according to Valcheva et al (2007). Furthermore, all the strains were subjected to the sequencing of a portion of the 16S rRNA-coding gene in order to confirm that they belonged to the species.…”
Section: Methodsmentioning
confidence: 99%
“…Through the elaboration of results obtained from plate counts the generation time was calculated to be 4 h. A few colonies at the highest dilutions were randomly picked at each monitoring time. Species identification was carried out by the analysis of the internal ribosomal spacers, as described by Valcheva et al (2007).…”
Section: Picozzi and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the conventional method using selective media is not ideal for monitoring fermentative processes from a quantitative aspect; it takes a relatively long period of time to get results and only the organisms that have the ability to survive in an artificial medium can be enumerated. As molecular biology techniques have been developed, quantitative PCR methods for detecting 16S rRNA gene sequences [2,4] or the 16S-23S intergenic spacer regions [20] have been developed using specific PCR primers. However, since these primers are often sensitive to little changes in annealing temperature, multiple gene amplification may occur and it can prevent accurate identification of microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Adeymo et al, (2014) similarly reported the characterisation of Lactobacillus plantarum using molecular methods by polymerase chain reaction (PCR) and amplification of 16S rDNA genes to confirm their identities from fermented cereals. Direct amplification of 16S-23S intergenic space regions (ISRs) or PCR with specific primer derived from L-ISR was reported to be useful for specific typing of Lactobacillus sanfranciscensis (Valcheva et al, 2006).…”
Section: Molecular Confirmation and 16s Rdna Sequence Analysis Of Lacmentioning
confidence: 99%